Xiaoyaosan Exerts Antidepressant-Like Effect by Regulating Autophagy Involves the Expression of GLUT4 in the Mice Hypothalamic Neurons - Yang, Fu-Rong; Zhu, Xiao-Xu; Kong, Ming-Wang; Zou, Xiao-Juan; Ma, Qing-Yu; Li, Xiao-Juan; Chen, Jia-Xu (Frontiers in Pharmacology, 2022)
Many studies have proven that depressive-like behaviors is related to autophagy and the expression of GLUT4 in the hypothalamus. Xiaoyaosan has been shown to exert antidepressant effects in a variety of ways, but its underlying mechanism by which Xiaoyaosan regulates autophagy as well as GLUT4 in the hypothalamus remains unclear. Thus, in this study, we established a mouse model of depression induced by chronic unpredictable mild stress (CUMS), and set up autophagy blockade as a control to explore the changes in autophagy in hypothalamic neurons in depressed mice and its effect on glucose transporter 4 (GLUT4) to investigate the regulating effect of Xiaoyaosan. We examined the effects of Xiaoyaosan on behaviors exhibited during the open field test, tail suspension test and sucrose preference test, and the changes in autophagy in hypothalamic neurons as well as changes in GLUT4 and the related indicators of glucose metabolism in CUMS-induced depressive mouse model.We found that CUMS- and 3-MA-induced mice exhibited depressive-like behavioral changes, with decreased LC3 expression and increased p62 expression, suggesting decreased levels of autophagy in the mouse hypothalamus. The expression of GLUT4 was also decreased, and it was closely related to the level of autophagy through Rab8 and Rab10. Nevertheless, after the intervention of Xiaoyaosan, the above changes were effectively reversed. These results show that Xiaoyaosan can regulate the autophagy in hypothalamic neurons and the expression of GLUT4 in depressed mice.